1981
DOI: 10.1093/nar/9.20.5443
|View full text |Cite
|
Sign up to set email alerts
|

The high salt form of poly(dG-dC)·poly(dG-dC) is left-handed Z-DNA: Raman spectra of crystals and solutions

Abstract: The laser-Raman spectra of crystalline d(CpGpCpGpCpG) and of aqueous poly(dG-dC).poly(dG-dC) in high salt (4M NaCl) and low salt (0.1M NaCl) solutions have been measured and compared. The spectra of the crystal and the high-salt solution show a striking congruence, which indicates clearly that the high-salt form of the aqueous polymer has the left-handed Z-DNA structure of the crystalline oligomer. These two spectra differ substantially from that of the low-salt form of the polymer, which has been found previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
142
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(161 citation statements)
references
References 9 publications
(8 reference statements)
17
142
0
Order By: Relevance
“…Changes in the cytosine bands between 1200 and 1280 cm -1 are also apparent. All these changes are in agreement with earlier Raman spectroscopic investigations of the B-and Z-form DNAs (Thamann et al, 1981;Benevides & Thomas, 1983).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Changes in the cytosine bands between 1200 and 1280 cm -1 are also apparent. All these changes are in agreement with earlier Raman spectroscopic investigations of the B-and Z-form DNAs (Thamann et al, 1981;Benevides & Thomas, 1983).…”
Section: Resultssupporting
confidence: 92%
“…In a high-salt environment, it was established, by means of CD and Raman spectra, that the polynucleotide has a left-handed double-helical structure (Pohl & Jovin, 1972;Thamann et al, 1981;Benevides & Thomas, 1983).…”
mentioning
confidence: 99%
“…circular dichroism experiments (1), has been confirmed by X ray crystal diffraction studies (2,3) and characterized by other various techniques: 31P and 1H NMR (4-7), Raman (8,9) and IR spectroscopy (9,10). In native systems, the existence of such conformations has been evidenced by indirect immunological techniques (12)(13)(14).…”
Section: Introductionmentioning
confidence: 83%
“…Crystals of several different sequences grown in a variety of conditions assume almost identical left-handed double-helical structures (Ho & Mooers, 1997). It has been shown that even the absence of high salt, earlier thought to be necessary (Pohl & Jovin, 1972;Thaman et al, 1981;Thomas & Peticolas, 1984), could be compensated by other factors such as methylation of cytosine (Behe & Felsenfeld, 1981;Malfoy et al, 1982;Jovin et al, 1983;Wang et al, 1985). Hexammine salts are helix-stabilizing agents (Ascoli et al, 1973;Eichorn, 1982;Hingerty et al, 1982).…”
Section: Number Of Contactsmentioning
confidence: 99%